The level of factionalism among elected barangay officials in the selected barangays of the municipality of Tanauan, Leyte. - Bagares, Jesabel Badem, et al.; Blanco, Desiree Lynn C. (Tacloban City Jeabel Badem Bagares, 2010)
This is a descriptive-correlational study on the Level of Factionalism among elected barangay officials in the selected barangays of the Municipality of Tanauan, Leyte. The objectives of the study include: (1) to identify the significant socio-econoic and demographic (SED) profile of the elected barangay officials in the selected barangays of Tanauan, Leyte, (2) to determine the level of factionalism among elected barangay officials in the selected barangays of Tanauan, Leyte; (3) to find out the relationship between SED factors and the level of factionalism among elected officials in Tanauan Leyte and (4) to discover the implication of the level of factionalism among elected barangay officials on barangay governance.
A simple random sampling was used in coming up with five sample barangays. The barangays involved in the study were Brgy. Buntay, Brgy. Canramos, Brgy. Magay, Brgy. San Miguel, and Brgy. Sto. Niño. The respondents include the Brgy. Chairman, seven Brgy. Councilors, and the SK Chairman of every barangay for a total of 45 respondent barangay officials for the five barangays. Self-administered questionnaires and unstructured interviews schedules were used as major research instruments in obtaining the data needed for the study. The gathered data were statistically processed and measured coming up with a result on the level of factionalism among elected barangay officials. Behaviors and judgments reflecting political ideology, political affiliation and loyalty and during decision making and policy implementation were used in measuring the level of factionalism among elected barangay officials. Correlation between Socio-economic and Demographic (SED) profile of the elected barangay officials and the level of factionalism was also established. Eta. value and Pearson product moment correlation (r-value) was used to establish relationships between socio-economic and demographic (SED) factors and the level of factionalism. It measured the relationship between sex, highest educational attainment, previous occupation and the level of factionalism while measuring the relationship between age and level of factionalism, Point Biserial was used.
The findings of the study include the following: (1) most of the respondents were males, and majority had finished secondary and tertiary education and were newly elected officials of their barangay, (2) political ideology and political affiliation and loyalty resulted the high level of factionalism since these are the usual sources of conflict among barangay officials and that in terms of policy decision making and its implementation, they work together for the welfare of the barangay, (3) among the socio economic and demographic factors, only age resulted the most significant in relation to the level of factionalism among elected barangay officials and (4) level of factionalism could affect governance in a way that barangay officials' performance affected by conflicts and group divides could level-off unity among the barangay officials in promoting the welfare and interests of the whole barangay.
The following policy recommendations are also encouraged: (1) this can also be an aid for future studies on factionalism in the Philippine context, since politics in the local and national level share the same political customs, (2) this study will become an aid to future researches particularly on behaviorism, and (3) this study will aid future researchers in determining in depth reasons as to why factionalism delays advancements in the society.
Undergraduate thesis (B.A.S.S. Political Science)--University of the Philippines, Tacloban
Keywords: Social Science